Understanding homeowner decision-making through demographics: Barriers to housing retrofit at scale - Chamara Panakaduwa; Paul Coates; Mustapha Munir (PLoS ONE, 2025)
Housing retrofit is vital for meeting sustainability goals, yet limited homeowner demand remains a significant barrier to widespread adoption. While challenges such as skills shortages and supply chain issues also exist, a strong homeowner demand could drive solutions to these obstacles. Despite the availability of grant schemes, homeowner interest in retrofitting remains low, slowing adoption rates and impeding national sustainability targets. Based on data from a questionnaire survey of UK homeowners, this study explores how demographic factors shape homeowner decision-making behaviour. Statistical analysis reveals several key insights: (1) homeowners primarily view retrofitting as an investment, seeking returns through energy bill savings; (2) concern over unintended consequences of retrofitting impacts willingness to participate; and (3) educational level strongly influences homeowner behaviour. These findings offer valuable perspectives for developing large-scale retrofit strategies, addressing the underlying behavioural barriers that have hindered the success of existing retrofit programs.